Acute Kidney Injury in COVID-19: 90 Days of the Pandemic in a Brazilian Public Hospital - Zamoner, Welder [UNESP]; Santos, Camilla Andrade da Silva [UNESP]; Magalhães, Luís Eduardo [UNESP]; Oliveira, Paula Gabriela Sousa de [UNESP]; Balbi, André Luis [UNESP]; Ponce, Daniela [UNESP] (Frontiers, 2021)
Renal involvement is frequent in COVID-19 (4–37%). This study evaluated the incidence and risk factors of acute kidney injury (AKI) in hospitalized patients with COVID-19. Methodology: This study represents a prospective cohort in a public and tertiary university hospital in São Paulo, Brazil, during the first 90 days of the COVID-19 pandemic, with patients followed up until the clinical outcome (discharge or death). Results: There were 101 patients hospitalized with COVID-19, of which 51.9% were admitted to the intensive care unit (ICU). The overall AKI incidence was 50%; 36.8% had hematuria or proteinuria (66.6% of those with AKI), 10.2% had rhabdomyolysis, and mortality was 36.6%. Of the ICU patients, AKI occurred in 77.3% and the mortality was 65.4%. The mean time for the AKI diagnosis was 6 ± 2 days, and Kidney Disease Improving Global Outcomes (KDIGO) stage 3 AKI was the most frequent (58.9%). Acute renal replacement therapy was indicated in 61.5% of patients. The factors associated with AKI were obesity [odds ratio (OR) 1.98, 95% confidence interval (CI) 1.04–2.76, p < 0.05] and the APACHE II score (OR 1.97, 95% CI 1.08–2.64, p < 0.05). Mortality was higher in the elderly (OR 1.03, 95% CI 1.01–1.66, p < 0.05), in those with the highest APACHE II score (OR 1.08, 95% CI 1.02–1.98, p < 0.05), and in the presence of KDIGO stage 3 AKI (OR 1.11, 95% CI 1.05–2.57, p < 0.05). Conclusion: AKI associated with severe COVID-19 in this Brazilian cohort was more frequent than Chinese, European, and North American data, and the risk factors associated with its development were obesity and higher APACHE II scores. Mortality was high, mainly in elderly patients, in those with a more severe disease manifestation, and in those who developed KDIGO stage 3 AKI.
Keywords: acute kidney injury; COVID-19; dialysis; mortality; risk factors